2013
DOI: 10.1080/15257770.2013.774014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Pyrrole Polyamide- 2′-Deoxyguanosine 5′-Phosphate Hybrid

Abstract: Pyrrole polyamide-2'-deoxyguanosine 5'-phosphate hybrid (Hybrid 4) was synthesized and evaluated in terms of the inhibition of mouse mammary carcinoma FM3A cell growth. Hybrid 4 was found to exhibit dose-dependent inhibition of cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The filtrate was evaporated to dryness to give 24 (2.14 g, quantitative yield) as a white powder, which was subsequently used without purification. 1 H-NMR (CDCl 3 ): δ 6.37 (s, 1H, and Im-H), 4.38 (2H, q, J = 7:1 Hz, and OCH 2 CH 3 ), 3.92 (3H, s, and NCH 3 ), 2.96 (brs, NH 2 , and 2H), and 1.40 (3H, t, J = 7:1 Hz, and OCH 2 CH 3 ); 13 (25). Compound 24 (2.09 g, 12.4 mmol) was dissolved in DMF (15 mL), and then a solution of di-tert-butyldicarbonate (5.42 g, 24.8 mmol) in DMF (10 mL) was added.…”
Section: Ethyl 1-methyl-4-nitroimidazole-2-carboxylate (21)mentioning
confidence: 99%
See 1 more Smart Citation
“…The filtrate was evaporated to dryness to give 24 (2.14 g, quantitative yield) as a white powder, which was subsequently used without purification. 1 H-NMR (CDCl 3 ): δ 6.37 (s, 1H, and Im-H), 4.38 (2H, q, J = 7:1 Hz, and OCH 2 CH 3 ), 3.92 (3H, s, and NCH 3 ), 2.96 (brs, NH 2 , and 2H), and 1.40 (3H, t, J = 7:1 Hz, and OCH 2 CH 3 ); 13 (25). Compound 24 (2.09 g, 12.4 mmol) was dissolved in DMF (15 mL), and then a solution of di-tert-butyldicarbonate (5.42 g, 24.8 mmol) in DMF (10 mL) was added.…”
Section: Ethyl 1-methyl-4-nitroimidazole-2-carboxylate (21)mentioning
confidence: 99%
“…From this result, it is expected that MGB polyamide-oligonucleotide conjugates could be effective gene expression control compounds and that MGB polyamide-2′-deoxyguanosine hybrid might be of potential use as a sequence-specific gene therapy agent based on potential obstruction of DNA replication and transcription. The inhibition of mouse mammary carcinoma FM3A cell growth by pyrrole polyamide compounds (Hybrids and distamycin A) has been evaluated ( Figure 1 ) [ 25 ]. It was found that hybrids induce dose-dependent inhibition of cell growth.…”
Section: Introductionmentioning
confidence: 99%